Corporate short-term financing in Europe : the role of trade credit and bank loans in liquidity management - Koralun-Berez??nicka, Julia (Routledge, Taylor & Francis Group, 2026)
Corporate Short-Term Financing in Europe offers a thorough analysis of how European companies manage liquidity, with a particular focus on trade credit and bank credit as key instruments. Drawing on rich cross-country data, this book examines the relationship between trade credit and short-term bank loans, analysing when firms substitute one for the other or use them together to optimise cash flow. With Europe's financial systems ranging from bank-based systems to market-driven economies, this study uncovers how firm size, industry, and national context shape short-term financing strategies. The book also addresses how financial crises and regulatory shifts affect corporate short-term funding decisions. Combining theoretical frameworks with empirical evidence, the book provides fresh insights for academics, policymakers, financial managers and business leaders concerned with corporate liquidity, SME support and financial resilience, and practitioners involved in credit risk assessment and working capital management. Essential reading for anyone managing short-term corporate finance in today's fast-changing environment.
Keywords: Corporations -- Finance -- Law and legislation -- Europe.; elektronické knihy; electronic books